Skład morfologiczny i właściwości nawozowe kompostów wytwarzanych z frakcji organicznej odpadów komunalnych w Zakładzie Utylizacji Odpadów Gorzów Wielkopolski = Morphological composition and fertilising properties of composts produced from organic fraction of municipal waste in ZUO Gorzów Wielkopolski - Meller, Edward; Sammel, Adam; Suchenia, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Morphological composition of composts produced from the 16-80 mm fraction of municipal waste in ZUO Gorzów Wielkopolski in the years 2004/2005 has been characterised in this paper. Basic fertilising compost properties have been also analysed: content of organic matter, total nitrogen, two macroelement forms (soluble in HCl at the concentration 0.5 mol?dm-3 and in concentrated HNO3 + HClO4 mixture). Compost were divided into two fractions with a diameter of below and above 1.0 mm.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); komposty; odpady; właściwości nawozowe; composts; wastes; fertilising properties